PENGARUH DANA PIHAK KETIGA, CAR, DAN NPL TERHADAP PENYALURAN KREDIT PT BTN TBK. CABANG MAKASSAR - MUHAMMAD NUR ABDI; RISNAYANTI RISNAYANTI; ASRIATI ASRIATI (Jurnal Ilmiah Manajemen "E M O R", 2020)
PT Bank Tabungan Negara as a financial institution that has a financial intermediation function. One function of financial intermediation is to channel credit to the community. Various problems related to banks related to distribution loans. This factor causes the author to do research on what factors are very important in channeling the amount of credit. Facing a large potential risk due to non-performing loans, banks are required to have good credit planning and distribution strategiesThis study studies what factors are driving the distribution of the amount of credit to the State Savings Bank PT. The data used in this study are primary and secondary data. Primary data obtained by interviews and direct observations on the related credit division. While secondary data is obtained from literature studies and data obtained from the company contains annual reports. Analysis using multiple linear regression by processing data using SPSS. 16.From this study, deposits were positively correlated with the distribution of credit amounting to 89.8%, CAR correlated positively with the distribution of credit amounting to 84.9%, and NPLs negatively correlated with the distribution of credit amounting to -9.6%. From the results of the tests conducted on this study indicate that the independent variables namely DPK, CAR and NPL significantly influence the Distribution of Credit with a significant level of 89.8%.